2012
DOI: 10.1242/jeb.070391
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic, locomotor, and sex-dependent effects of elevated temperature on Trinidadian guppies: limited capacity for acclimation

Abstract: SUMMARYGlobal warming poses a threat to many ectothermic organisms because of the harmful effects that elevated temperatures can have on resting metabolic rate (RMR) and body size. This study evaluated the thermal sensitivity of Trinidadian guppies (Poecilia reticulata) by describing the effects of developmental temperature on mass, burst speed and RMR, and investigated whether these tropical fish can developmentally acclimate to their thermal conditions. These traits were measured following exposure to one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…Endler, 1986; Langerhans and DeWitt, 2004; Langerhans, 2009) and how predator regimes influence features such as coloration, body shape, performance, and life history characteristics. Research has also begun to evaluate the roles of abiotic selective pressures, such as temperature (Lema and Nevitt, 2006; Muñoz et al, 2012; Nilsson et al, 2009), toxins (Riesch et al, 2010; Tobler et al, 2011), and salinity (Boeuf and Payan, 2001; Horppila et al, 2011) in driving population level differences in the morphology and physiology of fishes. Extreme environments should amplify the effects of divergent natural selection, as seen with livebearing fishes in the toxic sulfur pools of Mexico (Tobler et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endler, 1986; Langerhans and DeWitt, 2004; Langerhans, 2009) and how predator regimes influence features such as coloration, body shape, performance, and life history characteristics. Research has also begun to evaluate the roles of abiotic selective pressures, such as temperature (Lema and Nevitt, 2006; Muñoz et al, 2012; Nilsson et al, 2009), toxins (Riesch et al, 2010; Tobler et al, 2011), and salinity (Boeuf and Payan, 2001; Horppila et al, 2011) in driving population level differences in the morphology and physiology of fishes. Extreme environments should amplify the effects of divergent natural selection, as seen with livebearing fishes in the toxic sulfur pools of Mexico (Tobler et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that changes in environmental factors, such as water quality and temperature can elicit a decrease in size as a result of the allocation of energy towards processes involved with survival in that environment (Lema and Nevitt, 2006; Horppila et al . , 2011; Muñoz et al . , 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The positive effect of temperature at noon is more difficult to explain: Munoz et al . () demonstrated a ‘physiological tipping point’ for guppies exposed to 30 °C temperatures, where metabolic demands have a negative effect on growth and locomotion. Our data show that guppies continue to perform reproductive behaviours at temperatures in excess of these, however.…”
Section: Discussionmentioning
confidence: 99%
“…Taking advantage of wild‐caught fish and the natural abiotic variability of Trinidad, our approach enables us to explore the effects of temperature, coupled with light, on guppy activity patterns, and provides the opportunity to investigate temporal patterns in reproductive behaviour. Munoz, Breckels & Neff () demonstrate that at temperatures of around 30 °C the metabolic rate of guppies increases to the point where growth and locomotion becomes limited. Consequently, if temperature is an important driver of daily activity patterns, we hypothesize that reproductive behaviours will be highest in the morning, and suppressed in the middle of the day and afternoon when temperatures are still elevated.…”
Section: Introductionmentioning
confidence: 99%
“…; Pörtner and Knust ; Muñoz et al. ). Conversely, interindividual variation in the thermal response may be reflective of genetic variability in the underlying physiological processes.…”
Section: Introductionmentioning
confidence: 99%